Hesitancy and Refusal of the COVID-19 Vaccine Among Healthcare Professionals: A Cross-Sectional Study in a Portuguese Hospital - Teófilo, Vanessa (2025)
Introduction: Vaccine hesitancy is recognized by the World Health Organization as a major global health threat. In the context of the COVID-19 pandemic, this issue has taken on unique dimensions. Healthcare professionals are considered one of the most reliable sources of information regarding vaccination. Their stance on immunization is a determining factor in their likelihood to recommend it to others, with potential repercussions for vaccination uptake rates in the general population. This study aimed to characterize the sociodemographic profile of healthcare professionals at a Portuguese tertiary hospital who declined COVID-19 vaccination and to analyze the reasons for hesitancy/refusal and future vaccination intentions. Methods: A cross-sectional study was conducted in 2021, targeting healthcare professionals eligible for the completion of the primary COVID-19 vaccination schedule. Those who refused vaccination were asked to complete the “COVID-19 Non-Vaccination Questionnaire”, which included a multiplechoice question and an open response field regarding reasons for hesitancy/refusal and future vaccination intentions. Variables analyzed included gender, age, and professional category. Results: Among the 6648 healthcare professionals in the sample, 2.3% (n = 153) declined to complete the vaccination schedule. The average age was 46 years (SD = 11), with the proportion in each age group being 1.2% aged ≤ 35 years, 2.5% aged 36 - 45 years, and 3.1% aged > 45 years. The vaccine refusal rate among all professionals of each gender was 2.3% for females and 2.4% for males. A higher proportion of refusals was observed among healthcare assistants (n = 53, 4.0%) and technical assistants (n = 13, 3.0%). Sixteen reasons for vaccine hesitancy/refusal were identified, with the most frequently reported being fear of adverse reactions (n = 31), insufficient research on vaccines (n = 22), and distrust in vaccine efficacy (n = 25). Only 28.1% (n = 43) expressed an intention to be vaccinated in the future.Conclusion: A high acceptance rate for the primary COVID-19 vaccination schedule was observed. The likelihood of vaccine refusal was similar between genders but higher among individuals over 45 years and operational support staff. The reasons for vaccine refusal that implied concerns about the vaccine’s safety stood out. Further studies are needed to better understand the dynamics underlying vaccine hesitancy/refusal.